We care Sdn. Bhd. / Owais Qarni Qusham …[et al.] - Qusham, Owais Qarni; Supian Suri, Mohamad Azril; Rosli, Mohammad Syafiq; Ali Nordin, Muhamad Faris; Mazlan, Muhammad 'Abiddullah (2016)
We Care Sdn. Bhd. is a company that concern about the demand and needs of Malaysians especially to old folks and disable person. Therefore, we provide an easier medical transportation for them to use it everywhere they want. Besides that, we would make sure that the quality of the product will reach the expectation of the society with the good quality. Furthermore, we will make some upgrading in our product and others. We are not just looking for profits but we want to help people especially help our own country. With our product, we will provide the facility and also service to people. Our upgrade product will give better satisfaction to customers. It also can increase our country income by the tax that we pay and can also be an attractive to tourist with our service product. Moreover, we will create another job to citizen in Malaysia. We had decided to start our business at No. 10 Jalan Tun Teja 35/15, Alam Impian, 40470 Shah Alam, Selangor. The reasons we chose this location because the location was near the private and public hospitals, pharmacies and also residential area such as apartments and houses. So we think that this area is suitable for our product to invent in market.